Composite negative electrode active material ball

JP3250515UActive Publication Date: 2025-03-13PROLOGIUM TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025000071U
Authority / Receiving Office
JP · JP
Patent Type
Utility models
Current Assignee / Owner
Priority Date
2022-12-08
Filing Date
2025-01-09
Publication Date
2025-03-13
Estimated Expiration
2032-12-15

Smart Images

  • Figure 0003250515000001_ABST
    Figure 0003250515000001_ABST
Patent Text Reader

Abstract

The present invention provides a composite negative electrode active material sphere having a common conductive metal core, which is a negative electrode active material for a lithium battery. The present invention relates to a composite anode active material sphere (10) comprising a substantially porosity-free conductive metal core (12) and a plurality of silicon or silicon compound particles (14) distributed on the surface of the conductive metal core, with a portion of the volume of the silicon or silicon compound particles being embedded in the conductive metal core. During alloying and dealloying with lithium, the silicon or silicon compound particles can maintain good contact with the conductive metal core. Thus, the composite anode active material sphere has good electrical conductivity properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode active material for lithium batteries, and in particular to a composite negative electrode active material sphere having a common conductive metal core. [Background technology]

[0002] Lithium-ion batteries, due to their high energy density and / or long cycle life compared to other energy storage devices, are widely used in various products such as automobiles, wearable products for consumer and industrial applications, portable devices, energy storage devices, etc. These lithium-ion batteries are found in almost every area of ​​human daily life.

[0003] The anode active material commonly used in lithium-ion batteries is graphite. However, its theoretical discharge capacity is limited to about 360 mAh / g, limiting the use of graphite in high-capacity lithium batteries. Therefore, other materials that can be alloyed with lithium, such as silicon, are gradually replacing graphite as the anode active material in lithium-ion batteries. Although silicon has a theoretical capacity of 4200 mAh / g, which is significantly higher than that of graphite, silicon expands in volume by more than 300% during charging and discharging. The forces resulting from this expansion cause silicon to fracture along its crystals or boundaries.

[0004] Therefore, various new structures have been proposed to allow silicon to be applied to the negative electrode of lithium batteries. For example, silicon nanoparticles or nanowires can increase the surface area by minimizing the particle size. This releases the forces caused by expansion and avoids cracks. However, after nano-sizing silicon, more conductive materials and adhesives are required. Also, the proportion of active material that can undergo electrochemical reactions in the electrode is greatly reduced. Furthermore, nano-sizing silicon makes the surface area too large, making it difficult to disperse. It becomes more difficult to prepare a slurry. Furthermore, the larger the surface area, the larger the area of ​​the solid electrolyte interphase (SEI) layer with high resistance and the larger the amount of the SEI layer. This increases the consumption of lithium resources. Therefore, some nano-scale silicon is stacked and agglomerated to form a secondary microparticle structure. In this structure, the formation of the SEI layer can be avoided by the silicon located inside. When the volume of silicon changes due to the reaction with lithium, gaps are created between the silicon particles that are in contact with each other in the original state. As a result, lithium can no longer diffuse from the contact points between the silicon particles.

[0005] As another structure, micro-scale silicon spheres with nano-holes that can absorb volume expansion have been proposed. However, the surface area of ​​micro-scale silicon spheres with nano-holes is almost the same as that of nano-scale silicon spheres without holes if the weight is the same. Therefore, when the electrolyte penetrates into the nano-holes to form the SEI layer, the regeneration amount of the SEI layer and the consumption of lithium resources are large, which is a problem that remains.

[0006] In order to overcome the above drawbacks, SiO x It was suggested that fillers such as Si / C could be placed in the nanoholes. After formation, SiO x is Si and lithium silicate (LiSi x O y) is formed, and the lithium silicate is sandwiched between the Si. Si / C is a carbide present at the initial stage, which reduces the formation area for forming the SEI layer. However, the formation of lithium silicate also leads to lithium consumption. The presence of filler material reduces the overall Coulomb efficiency and reduces the utilization rate. Also, as in US Patent Application No. 16 / 514953, a composite structure using liquid metal that covers several types of nanoscale silicon powder has been proposed. The advantages of this structure are that the overall surface area is relatively small, the electrical conductivity is good, and the liquid metal can absorb the expansion. However, compared with the SEI layer formed on silicon and the electrolyte, the SEI layer formed by the liquid metal in contact with the electrolyte has insufficient structural stability and is prone to collapse. Furthermore, the Coulomb efficiency and utilization rate of the liquid metal in the electrochemical reaction are also insufficient. Therefore, a composite type negative electrode active material sphere is provided to overcome the above-mentioned problems of silicon. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] U.S. Patent Application Serial No. 16 / 514953 Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention aims to provide a composite negative electrode active material sphere, in which the silicon or silicon compound particles can maintain good contact with the conductive metal core through the embedded part when the silicon or silicon compound particles undergo volume change during alloying / dealloying with lithium, and therefore the composite negative electrode active material sphere can maintain good electron transfer properties.

[0009] Another object of the present invention is to provide a composite negative electrode active material sphere. The material of the conductive metal core is selected from materials that can be alloyed with lithium. Before assembling silicon or silicon compound particles, the surface of the conductive metal core can be pre-lithiated. Therefore, the conductive metal core is used as a lithium source to reduce the irreversible loss of lithium ions.

[0010] Another object of the present invention is to provide a composite negative electrode active material sphere, in which a shared SEI film is arranged between adjacent silicon or silicide particles, and most of the outer surface of the conductive metal core is covered with silicon or silicide particles, so that the loss of electrolyte is effectively reduced after the composite negative electrode active material sphere is adapted to a lithium battery.

[0011] Another object of the present invention is to provide a composite negative electrode active material sphere, in which a micro-scale conductive metal core is used as a carrier to which nano-scale silicon or silicon compound particles are attached, and the mixture of the negative electrode slurry for lithium batteries is micro-scaled for easy dispersion, which solves the problem that nano-scale silicon or silicon compound particles are easily agglomerated and difficult to disperse.

[0012] Another object of the present invention is to provide a composite negative electrode active material sphere, in which the hardness of the conductive metal core is lower than that of the silicon or silicon compound particles, so that the conductive metal core can deform to absorb the stress caused by the expansion of the silicon or silicon compound particles during charging and discharging. [Means for solving the problem]

[0013] In order to achieve the above object, the present invention discloses a composite negative electrode active material sphere, which includes a conductive metal core and a plurality of silicon or silicon compound particles distributed on the surface of the conductive metal core. The conductive metal core has a first average particle size at room temperature, and the silicon or silicon compound particles have a second average particle size. The silicon or silicon compound particles are in direct contact with the outer surface of the conductive metal core. Also, a part of the silicon or silicon compound particles is embedded in the conductive metal core. Therefore, during the volume change of the silicon or silicon compound particles, the silicon or silicon compound particles can maintain a state of direct contact with the conductive metal core. Therefore, the conductive metal core serves as a common internal conductive element of the silicon or silicon compound particles. Also, the first average particle size is more than 10 times the second average particle size.

[0014] Further scope of applicability of the present invention will become apparent from the detailed description set forth below. It should be understood, however, that the detailed description and specific examples, while indicating preferred embodiments of the present invention, are given by way of illustration only, since various changes and modifications within the spirit and scope of the present invention will become apparent to those skilled in the art from this detailed description. The present invention will be more fully understood from the following detailed description, which is given by way of example only and is not intended to be limiting of the present invention. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic diagram of a composite negative electrode active material ball according to the present invention; [Diagram 2] 2 is a schematic diagram of a composite negative electrode active material sphere of the present invention when fitted into a battery cell; [Diagram 3] FIG. 2 is a schematic diagram of a composite negative electrode active material sphere of the present invention, showing a state in which an SEI film is shared between adjacent silicon or silicon compound particles. [Figure 4] FIG. 2 is a schematic diagram of a composite anode active material sphere of the present invention, showing a portion of the silicon or silicon compound particle embedded in a conductive metal core. [Diagram 5]FIG. 2 is a schematic diagram of a composite anode active material sphere of the present invention, showing stacks of silicon or silicon compound particles of various sizes, with the silicon or silicon compound particles embedded in a conductive metal core. [Figure 6] FIG. 2 is a schematic diagram of a composite anode active material sphere of the present invention, showing stacks of silicon or silicon compound particles of various sizes, with the silicon or silicon compound particles embedded in a conductive metal core. [Figure 7] FIG. 2 is a schematic diagram of a composite negative electrode active material sphere of the present invention, showing a state in which a portion of the SEI film of silicon or silicon compound particles is shared. [Figure 8] FIG. 2 is a schematic diagram showing another embodiment of a composite negative electrode active material ball according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described with respect to certain embodiments and with reference to certain drawings, but the invention is not limited to the drawings, but only by the claims. Any reference signs in the claims should not be construed as limiting the scope. The drawings described are only schematic and are non-limiting. In the drawings, the dimensions of some of the elements may be exaggerated and not drawn to scale for illustrative purposes.

[0017] References throughout this specification to "one embodiment" or "an embodiment" mean that a particular feature, structure, or characteristic described in connection with an embodiment is included in at least one embodiment of the invention. Thus, the appearances of the phrases "in one embodiment" or "in an embodiment" in various places throughout this specification do not necessarily all refer to the same embodiment, but may all refer to the same embodiment. Furthermore, the particular features, structures, or characteristics may be combined in any suitable manner, in one or more embodiments, as will be apparent to one of ordinary skill in the art from this disclosure.

[0018] Please refer to FIG. 1. The present invention relates to a composite negative electrode active material sphere 10 including a conductive metal core 12 having almost no pores, a plurality of silicon or silicon compound particles 14 distributed on the surface of the conductive metal core 12, and a conductive material 16. As shown in FIG. 1, the silicon or silicon compound particles 14 are in direct contact with the surface of the conductive metal core 12. However, referring to FIG. 5 to FIG. 7, there may be other silicon or silicon compound particles 17 that are not in direct contact with the surface of the conductive metal core 12. These silicon or silicon compound particles 17 are stacked on the surface of the silicon or silicon compound particles 14 to further prevent the surface of the conductive metal core 12 that is not covered by the silicon or silicon compound particles 14 from being exposed. In this way, the contact area between the conductive metal core 12 and the electrolyte can be further reduced. For the silicon or silicon compound particles 14 that are in direct contact with the outer surface of the conductive metal core 12, a part (part of the volume) of the silicon or silicon compound particles 14 is embedded in the conductive metal core 12, i.e., they are not only in single-point contact or connection on the outer surface. The embedded portion of the silicon or silicon compound particles 14 is at least 10% of the total volume after formation. The conductive metal core 12 has a first average particle size and a first average hardness at room temperature, and the silicon or silicon compound particles 14 have a second average particle size and a second average hardness. The first average particle size is more than 10 times the second average particle size. The first average particle size is in the range of 0.1 micrometers to 50 micrometers, and the second average particle size is in the range of 10 nanometers to 500 nanometers. The second average hardness is higher than the first average hardness so that a part (part of the volume) of the silicon or silicon compound particles 14 is easily embedded in the conductive metal core 12. As shown in FIG. 4, the silicon or silicon compound particles 14 in direct contact with the outer surface of the conductive metal core 12 include an exposed portion 14a exposed from the conductive metal core 12 and an embedded portion 14b embedded in the conductive metal core 12. Therefore, when the volume of the silicon or silicon compound particle 14 changes due to alloying / dealloying caused by the extraction and insertion of lithium ions, the silicon or silicon compound particle 14 that is in direct contact with the outer surface of the conductive metal core 12 maintains direct contact with the conductive metal core 12 via the embedded portion 14b, allowing the composite negative electrode active material sphere 10 to maintain good electron transfer properties.Therefore, it is possible to efficiently solve the problem of electrically conductive voids caused by the volume change of the silicon or silicon compound particles 14. For example, voids may occur due to repeated volume expansion and contraction during alloying / dealloying of the silicon or silicon compound particles 14. When the volume of the silicon or silicon compound particles 14 expands, the conductive additives such as carbon black and carbon nanotubes are pushed away. When the volume of the silicon or silicon compound particles 14 shrinks to its original size or cracks, a gap appears between the conductive additive that has moved and the silicon or silicon compound particles 14. Electrons cannot be transported across this gap, which is called a "void."

[0019] The conductive material 16 is in direct contact with the conductive metal core 12 or the silicon or silicide particles 14, or both. In the present invention, when the conductive material 16 is in direct contact with the conductive metal core 12, it is possible to transport electrons to the silicon or silicide particles 14 via the conductive metal core 12, or to transport electrons out of the silicon or silicide particles 14. This allows the conductive metal core 12 to carry the common internal electrical element of the silicon or silicide particles 14.

[0020] Furthermore, the material of the conductive metal core 12 is selected from materials capable of alloying with lithium at a first potential, and the silicon or silicon compound particles 14 are capable of alloying with lithium at a second potential. The first potential is different from the second potential. Preferably, the first potential is higher than the second potential. Thus, when the silicon or silicon compound particles 14 are alloyed or dealloyed with lithium, the conductive metal core 12 remains in a passive state in which it does not alloy with lithium. In this passive state, the conductive metal core 12 serves as a diffusion host for lithium. The diffused lithium appears as an alloy in the conductive metal core 12, expanding the lithium retention of the composite negative electrode active material sphere 10. Furthermore, the diffused lithium in the conductive metal core 12 may expand toward the silicon or silicon compound particles 14 and serve as a lithium source. As described above, the conductive metal core 12 is capable of alloying with lithium ions. Thus, before the silicon or silicon compound particles 14 are assembled, the surface of the conductive metal core 12 is subjected to a lithium diffusion or doping process, also called pre-lithiation. The conductive metal core 12 and the silicon or silicon compound particles 14 are then mixed to prepare the composite anode active material sphere 10 of the present invention. The mixing method may be a ball mill process in which a portion of the silicon or silicon compound particles 14 is pressed and embedded into the conductive metal core 12. In practice, the composite anode active material sphere 10 is utilized in a battery cell. The pre-lithiated conductive metal core 12 is used as a lithium source to reduce the irreversible loss of lithium ions during charging and discharging of the battery cell.

[0021] Also, as shown in Figures 5 and 6, silicon or silicon compound particles 14 and 17 of various sizes are stacked. The silicon or silicon compound particles 14 that are placed directly on or in contact with the conductive metal core 12 will be partially embedded in the conductive metal core 12. The surface of the conductive metal core 12 is pressed against the silicon or silicon compound particles 14 to form an indentation 19. The silicon or silicon compound particles 14 of various sizes may be filled or stacked in the indentation 19. In Figure 5, the silicon or silicon compound particles 14 of small size are in contact with the indentation 19. The silicon or silicon compound particles 17 of large size are stacked on the surface of the silicon or silicon compound particles 14 of small size. In Figure 6, the silicon or silicon compound particles 14 of small and large size are in contact with the indentation 19.

[0022] The conductive metal core 12 is made of a low melting point metal, which is an alloy formed by mixing at least two materials selected from indium (melting point 156.6°C), tin (melting point 231.9°C), aluminum (melting point 660.4°C), bismuth (melting point 271.4°C), or germanium (melting point 937.7°C). The low melting point metal means an alloy with a melting point of less than 232°C. For example, the alloy has a composition of 45% tin and 55% bismuth, and has a melting point of about 150°C. The hardness of the low melting point metal is lower than that of the silicon or silicide particles 14. That is, the low melting point metal is softer than the silicon or silicide particles 14. Therefore, the conductive metal core 12 may be deformed by pressure from the silicon or silicide particles 14. Further, referring to FIG. 1, the conductive metal core 12 is illustrated as a circle. In practice, the conductive metal core 12 may be formed in any other geometric pattern or irregular shape. Furthermore, by changing the composition of the conductive metal core 12, the conductive metal core 12 may exhibit a certain softness at the operating temperature of the battery cell. The conductive metal core 12 can be deformed to absorb the expansion of the silicon or silicide particles 14, or even fill the cracks in the silicon or silicide particles 14 and 17 caused by the expansion. When the silicon or silicide particles 14 shrink in volume during dealloying, the filled metal is squeezed out. The squeezed out metal can then serve as a new conductive contact for the silicon or silicide particles 14 and 17.

[0023] The material of the silicon or silicon compound particles 14 and 17 is selected from any silicon-based anode active material, such as pure silicon, silicon oxide, silicon nitride, or any combination. The distribution of various particle sizes allows the silicon or silicon compound particles 14 to be placed on the surface of the highly cohesive conductive metal core 12 to improve surface coverage. For example, at least 50%, preferably more than 85%, of the outer surface of the conductive metal core 12 is covered or shielded by the silicon or silicon compound particles 14. The particle size of the silicon or silicon compound particles 14 is in the range of 10 to 500 nanometers. The nanoscale silicon or silicon compound particles 14 have a high surface area to volume ratio, which increases the reaction area for lithium ions to contact and intercalate. However, due to their cohesion, the nanoscale silicon or silicon compound particles 14 are difficult to disperse in the electrode slurry, which is a major obstacle in practical use. Therefore, the present invention utilizes the highly cohesive conductive metal core 12 as a carrier to which the nanoscale silicon or silicon compound particles 14 are attached. The main dispersion of the electrode slurry is the microscale composite negative electrode active material spheres 10, not the nanoscale silicon or silicon compound particles 14. This makes it possible to overcome the drawback that nanoscale particles tend to aggregate and are difficult to disperse.

[0024] The conductive material 16 of the present invention can include carbon nanotubes, graphene, carbon fiber, carbon black, graphite particles, natural graphite, artificial graphite, acetylene black, ketjen black, metal powder, or conductive polymer. The conductive material 16 is not limited to the above-mentioned materials as long as it is a conductive material applicable to lithium batteries. When the conductive material 16 contacts the conductive metal core 12, electrons can be transferred to or from the silicon or silicon compound particles 14 in contact with the conductive metal core 12. The conductive material 16 can also be mixed with the silicon or silicon compound particles 14 and placed on the conductive metal core 12.

[0025] Please refer to FIG. 2, which is a schematic diagram of a battery cell using a composite negative electrode active material sphere. As shown in the figure, the composite negative electrode active material sphere 10 is mixed with a binder (not shown) and applied to the surface of a negative electrode current collector 222 to form a negative electrode 22. The battery cell 20 also includes a positive electrode 24 and a separator 26 disposed between the negative electrode 22 and the positive electrode 24. The positive electrode active material 242 of the positive electrode 24 may be selected from any material used in the art without any restrictions. For example, as the positive electrode active material, a compound capable of inserting and extracting lithium ions, for example, a compound containing lithium and a material selected from cobalt, nickel, manganese, and combinations thereof, may be used.

[0026] The conductive material and / or binder of the positive electrode 24 may be the same as or different from that of the negative electrode 22. The separator 26 disposed between the negative electrode 22 and the positive electrode 24 may be made of any material available in the art, for example, a material that has low resistance to ion movement in the electrolyte. For example, the separator 26 may be in the form of a plate that separates the negative electrode 22 and the positive electrode 24, and may be made of a material selected from glass fiber, polyester, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), and combinations thereof, each of which may be a perforated nonwoven or woven fabric. The separator 26 may be a solid electrolyte. In FIG. 2, the packaging members of the battery cell 20 include a positive electrode current collector 244, a negative electrode current collector 222, and an adhesive frame 28 sandwiched between the positive electrode current collector 244 and the negative electrode current collector 222 to isolate the electrodes from the external environment. However, this does not limit the use of the composite negative electrode active material ball 10 of the present invention only in such a battery cell. The composite negative electrode active material sphere 10 can be widely used in various battery cells or battery structures that use silicon-based materials as the negative electrode active material.

[0027] Please refer to FIG. 3 and FIG. 1. As shown in the figures, when a battery made of the composite negative active material sphere 10 of the present invention is charged and discharged, a solid electrolyte interface (SEI) film 18 is formed on the surface of the composite negative active material sphere 10. The SEI film 18 is formed on the surface of a material that can be alloyed with lithium when it comes into contact with an electrolyte. In the present invention, most of the outer surface of the conductive metal core 12 is covered with silicon or silicon compound particles 14, which effectively reduces contact with the electrolyte and forms an SEI film. Thus, electrolyte loss is reduced. Furthermore, the SEI film 18 between two adjacent silicon or silicon compound particles 14 is a shared SEI film 18a, which is the part marked by the dotted line area a in the figure. Due to the existence of the shared SEI film 18a, the amount of the SEI film 18 is reduced compared to that of separate silicon or silicon compound raw material particles. Thus, electrolyte loss is further reduced. In FIG. 7, silicon or silicon compound particles 14 and 17 of various particle sizes are stacked on the surface of the conductive metal core 12. A shared SEI film 18a exists between portions of the SEI film 18 of adjacent silicon or silicon compound particles 14 and 17.

[0028] The SEI film formed on the surface of the silicon or silicon compound particles 14 and 17 is thinner, more stable, and easier for lithium ions to pass through than the SEI film formed directly on the surface of the conductive metal core 12. This leads to an improvement in the coulombic efficiency of the silicon or silicon compound particles 14 and 17. Compared with the specification of US Patent Application No. 16 / 514953, in which the silicon or silicon compound particles are completely coated with a low melting point metal, the surface of the conductive metal core 12 of the present invention is mostly coated with the silicon or silicon compound particles 14. The contact area between the conductive metal core 12 and the electrolyte can be greatly reduced. In addition, the present invention also reduces the proportion of poor SEI films formed directly on the surface of the conductive metal core 12, which are not suitable for the passage of lithium ions.

[0029] 8, a carbide shell 32 is formed on at least a portion, for example 75%, of the surface of the silicon or silicon compound particle 14 to minimize direct contact between the electrolyte and the silicon or silicon compound particle 14. This reduces electrolyte decomposition caused by terminal bonds on the silicon surface. Preferably, the carbide shell 32 is formed on more than 90% of the surface of the silicon or silicon compound particle 14.

[0030] Therefore, the present invention provides a composite anode active material sphere comprising a substantially pore-free conductive metal core and a plurality of silicon or silicon compound particles distributed on the surface of the conductive metal core. A portion of the silicon or silicon compound particles that are in direct contact with the outer surface of the conductive metal core is embedded in the conductive metal core. When the volume of the silicon or silicon compound particles changes due to alloying / dealloying associated with lithium ion extraction and insertion, the silicon or silicon compound particles maintain direct contact with the conductive metal core through the embedded portion, and the composite anode active material sphere maintains good electron transfer properties. In addition, a shared SEI film exists between adjacent silicon or silicon compound particles. Since most of the outer surface of the conductive metal core is covered with silicon or silicon compound particles, electrolyte loss is efficiently reduced. Furthermore, the material of the conductive metal core is selected from materials that can be alloyed with lithium ions. Before assembling the silicon or silicon compound particles, a pre-lithiation process can be performed on the surface of the conductive metal core. Thus, the conductive metal core serves as a lithium source to reduce irreversible loss of lithium ions. Alternatively, the conductive metal core can act as a diffusion host for lithium, expanding the lithium receiving or releasing capacity of the composite negative electrode active material spheres and improving the operating performance of the electrochemical system. Therefore, the battery cell made of the composite negative electrode active material spheres of the present invention can exhibit excellent reproducibility of charge and discharge performance based on the above-mentioned advantages.

[0031] Having described the invention, it will be apparent that the same may be modified in many ways. Such modifications should not be regarded as departing from the spirit and scope of the invention, and all such modifications as would be obvious to one skilled in the art are intended to be included within the scope of the following claims.

Claims

1. A composite type negative electrode active material sphere, the composite type negative electrode active material sphere comprising: a conductive metal core having a first average particle size at room temperature; a plurality of silicon or silicon compound particles having a second average particle size, distributed on a surface of the conductive metal core, directly contacting an outer surface of the conductive metal core, and partially embedded in the conductive metal core, the conductive metal core serving as a common internal conductive element of the silicon or silicon compound particles; and a solid electrolyte interface (SEI) film formed on the surface of the composite negative electrode active material sphere and having an SEI film shared between adjacent silicon or silicon compound particles; the first average particle size is microscale and the second average particle size is nanoscale, and the first average particle size is greater than 10 times the second average particle size; Composite negative electrode active material sphere.

2. 2. The composite negative electrode active material ball according to claim 1, wherein the conductive metal core is made of a metal having a low melting point of less than 232°C.

3. 3. The composite negative electrode active material ball according to claim 2, wherein the conductive metal core is an alloy formed by mixing at least two materials selected from the group consisting of indium, tin, aluminum, bismuth, and germanium.

4. 2. The composite negative electrode active material sphere according to claim 1, wherein the material of the silicon or silicon compound particles is selected from the group consisting of pure silicon, silicon oxide, silicon nitride, and combinations thereof.

5. 2. The composite negative electrode active material sphere according to claim 1, wherein the silicon or silicon compound particles have a particle size in the range of 10 to 500 nanometers.

6. 2. The composite negative electrode active material sphere of claim 1, wherein the conductive metal core is substantially free of pores.

7. The composite negative electrode active material sphere of claim 1, wherein the conductive metal core is capable of alloying with lithium ions at a first potential, and the silicon or silicon compound particles are capable of alloying with the lithium ions at a second potential, the first potential being higher than the second potential.

8. 2. The composite negative electrode active material ball according to claim 1, further comprising a conductive material, a portion of which is in direct contact with the outer surface of the conductive metal core.

9. 2. The composite negative electrode active material sphere according to claim 1, wherein at least 50% of said outer surface of said conductive metal core is covered with said silicon or silicon compound particles.

10. 2. The composite negative electrode active material sphere according to claim 1, wherein the first average particle size is in the range of 0.1 to 50 micrometers, and the second average particle size is in the range of 10 to 500 nanometers.

11. 2. The composite negative electrode active material sphere according to claim 1, wherein the embedded portion of the silicon or silicon compound particles occupies at least 10% of the total volume after formation.

12. 2. The composite negative electrode active material sphere according to claim 1, wherein the first average particle size is in the range of 0.1 to 50 micrometers.

13. 2. The composite negative electrode active material sphere according to claim 1, wherein at least 85% of said outer surface of said conductive metal core is covered with said silicon or silicon compound particles.

14. 2. The composite negative electrode active material sphere according to claim 1, wherein a carbide shell is formed on at least a portion of the surface of the silicon or silicon compound particle.

15. 15. The composite negative electrode active material sphere of claim 14, wherein the carbide shell forms on at least 75% of the surface of the silicon or silicon compound particle.

Citation Information

Patent Citations

  • Inorganic conductive layers for electrochemical cells

    US20200036001A1